Jobsheet Elektronik berbasis Project Based Learning Matakuliah Pemograman berorientasi Objek - Rini Widyastuti; Karmila Suryani; Ade Fitri Rahmadani; Diva Mawaddah; Ikhsan Akbar (Jurnal Pendidikan Informatika (EDUMATIC), 2023)
One of the practicum courses in the Informatics and Computer Engineering Education Study Program (PTIK) is Object-Oriented Programming. Practical learning still uses printed job sheets, so the practical process is less systematic. The research aims to produce a valid and practical electronic job sheet based on project-based learning (PjBL) in object-oriented programming courses. The research method used is research and development with the four-dimensional development model, namely: define (definition), design (design), develop (development), and disseminated (deployment). The research instruments were a validity sheet and a practicality questionnaire. The data analysis technique used is descriptive analysis in the form of percentage validity tests and practicality tests. The validity analysis was carried out by design experts and material experts, while the practicality analysis was completed by 23 students of the PTIK FKIP Bung Hatta University study program. The result of this research is a PjBL-based electronic job sheet, which was declared valid by validators at 86% based on aspects of presentation, writing, programming, content, and language. The practicality results that students fill out on the electronic job sheet meet the practical criteria of 84.6% in terms of usage, benefits, appearance, and language aspects. Therefore, this jobsheet can be used according to student needs as a digital learning resource in practical activities.